2009
DOI: 10.1002/jcp.21745
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia stimulates vesicular ATP release from rat osteoblasts

Abstract: Many neuronal and non-neuronal cell types release ATP in a controlled manner. After release, extracellular ATP (or, following hydrolysis, ADP) acts on cells in a paracrine manner via P2 receptors. Extracellular nucleotides are now thought to play an important role in the regulation of bone cell function. ATP (and ADP), acting via the P2Y(1) receptor, stimulate osteoclast formation and activity, whilst P2Y(2) receptor stimulation by ATP (or UTP) inhibits bone mineralization by osteoblasts. We found that rat cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 49 publications
8
140
1
Order By: Relevance
“…Controlled ATP release has been demonstrated from numerous excitatory and non-excitatory cells. In the bone microenvironment, osteoblasts (Buckley et al, 2003;Genetos et al, 2005;Orriss et al, 2009;Romanello et al, 2001;Rumney et al, 2012), osteoclasts and MLO-Y4 osteocyte-like cells (Genetos et al, 2007;Kringelbach et al, 2014) have all been shown to constitutively release ATP.…”
Section: Extracellular Nucleotides and The Regulation Of Bone Mineralmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled ATP release has been demonstrated from numerous excitatory and non-excitatory cells. In the bone microenvironment, osteoblasts (Buckley et al, 2003;Genetos et al, 2005;Orriss et al, 2009;Romanello et al, 2001;Rumney et al, 2012), osteoclasts and MLO-Y4 osteocyte-like cells (Genetos et al, 2007;Kringelbach et al, 2014) have all been shown to constitutively release ATP.…”
Section: Extracellular Nucleotides and The Regulation Of Bone Mineralmentioning
confidence: 99%
“…Since then several studies have indicated that the primary method of ATP release from osteoblasts is by vesicular exocytosis (Genetos et al, 2005;Orriss et al, 2009;Romanello et al, 2005). However, it has been suggested that the P2X7 receptor may also be involved (BrandaoBurch et al, 2012).…”
Section: Atp Release From Osteoblastsmentioning
confidence: 99%
“…Osteoblasts release ATP constitutively [44,45] and can generate low micromolar concentrations of adenosine in vitro [21,27]. Therefore, the possibility remains that endogenous adenosine exerts effects on osteoblasts that are not enhanced further by the addition of exogenous adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…There are substantial evidence for vesicular release from neuronal [22] and endocrine tissues [23]. Vesicular release has likewise been suggested to occur in non-excitable cells such as endothelial cells [24] and osteoblasts [25], but non-vesicular release is thought to contribute in a major way to ATP release in many cell types. The molecular identity of the ATP release channel is unknown, but potential candidates include large anion channels, cystic fibrosis transmembrane conductance regulator (CFTR), and hemichannels like connexins and pannexin-1, which have been suggested to form ATP-releasing units together with the ATP-gated ion channel P2X7 [26][27][28].…”
Section: The Unknown Mechanism Of Releasementioning
confidence: 99%